Unveiling Trichoderma's Secrets: Transforming Plant Health Management - Singh, Ankit Kumar; Singh, Ramji; Dixit, Pooshpendra Singh (Research Advances and Challenges in Agricultural Sciences Vol. 9, 2024)
The use of chemical pesticides in agricultural practices has led to significant concerns related to health and the environment in the last few decades. Consequently, there has been a growing interest in finding alternative approaches for controlling pests and diseases that are effective and environmentally friendly. Among these alternatives, Trichoderma has gained attention due to its remarkable ability to combat various crop pathogens in sustainable form. This study aims to evaluate the revolutionary role of Trichoderma in sustainable plant health management. Biocontrol agents have gained prominence as eco-friendly substitutes for conventional chemical pesticides in disease management and crop improvement. T. harzianum a common filamentous fungus, has emerged as a promising biocontrol agent due to its multifaceted strategies for suppressing diseases and promoting crop growth. Through improving nutrient absorption, enhancing soil structure, and producing growth-promoting chemicals like auxins and cytokinins, Trichoderma promotes plant growth. The effectiveness of Trichoderma in treating a variety of plant diseases brought on by bacteria, nematodes, and fungi has been proven through field research. Trichoderma offers long-lasting protection by establishing a beneficial presence early in the plant's life cycle, whether it is applied as a foliar spray, soil treatment, or seed treatment. In conclusion, Trichoderma holds immense potential as a biocontrol agent to safeguard crops sustainably. Trichoderma species play a pivotal role in managing plant diseases due to their versatile mechanisms. As global agriculture seeks alternatives to chemical pesticides, leveraging Trichoderma's potential offers a valuable avenue toward resilient and environmentally safe crop production.